Searching for a more valid form of parental rating scales of preschoolers' intellectual giftedness - development and validation of the Preschooler's Ability Rating Scale (PARS) - Jabůrek, Michal; Cígler, Hynek; Portešová, Šárka; Ťápal, Adam (Československá psychologie, 2021)
Objectives. The aim of this study was to develop a new parental rating scale for identification of intellectually gifted preschoolers (4 to 6 years of age). This new scale, the Preschooler's Ability Rating Scale (PARS), consists of two parts – PARS-PRE, which follows the principle of precocity and inquires about the age at which giftedness-relevant behavior appeared for the first time; and PARS-CUR, which focuses on the current level of abilities. Participants and setting. In total, 263 Czech mothers and 90 children participated in the main study. Hypotheses. PARS will have a two-dimensional structure corresponding to its two parts. Both parts will significantly correlate with scores on the Woodcock-Johnson: International edition II (WJ IE II COG). Statistical analysis. 1. Item analysis; 2. Exploratory factor analysis; 3. Correlational analyses with WJ IE II COG; 4. ROC analysis to evaluate the specificity and sensitivity. Results. Factor analysis suggests a three-factor structure – two of the factors correspond to the scale's original parts, and the third factor reflects early reading and counting (4 items from the precocity part). The diagnostic accuracy of the first two factors is similarly low (rPRE = .33, rCUR = .25), but substantially higher for the early reading/counting factor (rLIT = .52). Additionally, parental ratings are, in general, based more on children's verbal abilities than their nonverbal abilities. Given the low criterial validity, the authors do not recommend utilizing the PARS scale in a practical setting, however, the conclusions are useful for further development of similarly-minded scales. Study limitations. Only 90 children were administered the WJ IE II COG – the small sample size affects the precision of parameter estimates. The parentsʼ sample consists only of mothers. Downloads PDF Published 2021-08-29 How to Cite Jabůrek, M., Cígler, H., Portešová, Šárka, & Ťápal, A. (2021). Searching for a more valid form of parental rating scales of preschoolers' intellectual giftedness – development and validation of the Preschooler's Ability Rating Scale (PARS). Československá Psychologie, 65(4), 317-335. https://doi.org/10.51561/cspsych.65.4.317 Issue Vol. 65 No. 4 (2021) Section Articles License Copyright (c) 2021 Michal Jabůrek, Hynek Cígler, Šárka Portešová, Adam Ťápal Creative Commons License This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.
Keywords: nadání; Parents; Aptitude; lidé; škály posuzující chování; předškolní dítě; Behavior Rating Scale; rodičovské hodnocení dětí; Child, Preschool; rodiče; Humans